2015
DOI: 10.2139/ssrn.2719441
|View full text |Cite
|
Sign up to set email alerts
|

Disease Control and Inequality Reduction: Evidence from a Tuberculosis Testing and Vaccination Campaign

Abstract: This paper examines the economic impact of a tuberculosis control program launched in Norway in 1948. In the 1940s, Norway had one of the highest tuberculosis infection rates in Europe, affecting about 85 percent of the inhabitants. To lower the disease burden, the Norwegian government launched a large-scale tuberculosis testing and vaccination campaign that substantially reduced tuberculosis infection rates among children. We find that cohorts in school during and after the campaign in municipalities with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…High correlations between fathers and sons indicate that family background is a strong predictor of the next generation's success, whereas small correlations indicate that parents' status is not as important-in other words, there is more equality of opportunity when intergenerational correlations are low. 10 Bütikofer et al (2019) considered the introduction of Norwegian mother and child health centers, exploiting the fact that the timing of center openings varied substantially across locations, whereas Bütikofer and Salvanes (2015) studied the effects of a Norwegian tuberculosis control campaign making use of the fact that the campaign should have had a bigger effect in geographic areas that had higher precampaign tuberculosis levels. Although both studies focused on how the interventions improved treated cohorts' later life health and earnings, they also found that the interventions reduced the intergenerational persistence of educational attainment by 10% to 14%.…”
Section: Positive Policy Interventionsmentioning
confidence: 99%
“…High correlations between fathers and sons indicate that family background is a strong predictor of the next generation's success, whereas small correlations indicate that parents' status is not as important-in other words, there is more equality of opportunity when intergenerational correlations are low. 10 Bütikofer et al (2019) considered the introduction of Norwegian mother and child health centers, exploiting the fact that the timing of center openings varied substantially across locations, whereas Bütikofer and Salvanes (2015) studied the effects of a Norwegian tuberculosis control campaign making use of the fact that the campaign should have had a bigger effect in geographic areas that had higher precampaign tuberculosis levels. Although both studies focused on how the interventions improved treated cohorts' later life health and earnings, they also found that the interventions reduced the intergenerational persistence of educational attainment by 10% to 14%.…”
Section: Positive Policy Interventionsmentioning
confidence: 99%